2018
DOI: 10.1002/mdc3.12636
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Rating Scales for Urinary Symptoms in Parkinson Disease: Critique and Recommendations

Abstract: Background The prevalence of lower urinary tract symptoms (LUTS) is high in Parkinson's disease (PD). These problems negatively affect quality of life and include both storage and voiding problems. The International Parkinson and Movement Disorder Society established a task force to review clinical rating scales/questionnaires for the assessment of urinary symptoms in PD. Methods According to prespecified criteria, these scales/questionnaires were classified as “Recommended” or “Recommended with caveats” when … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 86 publications
0
12
0
Order By: Relevance
“…Identification of these patients with early PD is crucial for developing therapeutic strategies to prevent complications. Some validated questionnaires and clinical rating scales are useful for easily detecting and characterizing autonomic symptoms in clinical practice [ 8 ]. The Scales for Outcomes in Parkinson's Disease-Autonomic dysfunction (SCOPA-AUT) is a clinical questionnaire that assesses the presence and frequency of autonomic symptoms in patients with PD [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Identification of these patients with early PD is crucial for developing therapeutic strategies to prevent complications. Some validated questionnaires and clinical rating scales are useful for easily detecting and characterizing autonomic symptoms in clinical practice [ 8 ]. The Scales for Outcomes in Parkinson's Disease-Autonomic dysfunction (SCOPA-AUT) is a clinical questionnaire that assesses the presence and frequency of autonomic symptoms in patients with PD [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other researchers have also utilized the IPSS questionnaire to evaluate LUTS in Parkinson disease patients and found it useful irrespective of the patient"s gender. 6,12,13 There are many PD rating scales in use for staging the Parkinson"s disease severity. We utilized the Unified Parkinson"s Disease Rating Scale (UPDRS), which is a validated and standardized questionnaire for the holistic assessment of the severity and impact of PD on the patient.…”
Section: Discussion:-mentioning
confidence: 99%
“…LUTS are generally stratified using the IPSS into mild (1-7), moderate (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) and severe (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35). (Tables 2) This categorization was applied to the patient with PD in our study and it was observed that most of the patients had mild to moderate symptoms.…”
Section: Discussion:-mentioning
confidence: 99%
“…The Scales for Outcomes in Parkinson's Disease-Autonomic (SCOPA-AUT) specifically addresses autonomic dysfunction in PD and is perhaps the most frequently used scale for this purpose. Other scales have been developed for the assessment of individual features of autonomic dysfunction but, generally, have not been validated specifically for PD [8,9]. The Movement Disorder Society-Unified Parkinson's Disease Rating Scale (MDS-UPDRS) contains questions pertaining to autonomic dysfunction, some of which correlate well with the SCOPA-AUT [10].…”
Section: Introductionmentioning
confidence: 99%